The role of the mediator of personality traits in the relationship between the family of origin’s Intimacy and academic procrastination - Ebrahimi, Seyed Mohsen; Mohammadzadeh Adamalaei, Rajabali; Sadeghi, Jamal; Abbasi Esfanji, Aliasghar (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the mediating role of personality traits in the relationship between the family of origin’s Intimacy and academic procrastination. Method: For this purpose, 300 male and female students of Babol Azad University completed the available family of origin’s Scale (FOS), Academic Procrastinationscale (APS) and measure five personality traits (NEO-FFI) questionnaires. Data were analized using path analysis, through Bootstrap test and structural equation modeling. Results: Based on the research findings, all personality traits neuroticism, extroversion, Openness, agreeableness and conscientiousness were able to play a mediating variable in relation to the family of origin’s Intimacy and academic procrastination. But, personality traits neuroticism had a negative effect. Conclusion: In fact, it can be said that in a healthy family, the growth of intimacy, and the development of self-confidence will lead to the formation of personality traits such as activism, conscientiousness and empathy, all of which, in turn, are effective in academic achievement and reducing academic procrastination. While people with traits of neuroticism with a greater sense of insecurity, anxiety, usually with conflict, prevent the creation of an environment full of happiness and reduce the sensitivity of people to each other, also reduces the trust between them. Also, instead of expressing emotions logically, with more aggressive and hostile behavior, they hinder acadamic achievement and increase procrastination.